BIOACOUSTICS OF BATS IN VILCANOTA - URUBAMBA RIVER, CUSCO - RIVERA GARCÍA, Antony Andree (2024)
A guide to the echolocation pulses of 42 bat species recorded at eight stations near the Vilcanota‑Urubamba River, Cusco region, is presented. The objectives included optimizing the collection of clean, species‑specific acoustic recordings and developing an acoustic library in Peru. The flight tunnel is proposed as a more effective technique than the flight box, as it allows sustained flight in a single direction and the capture of high‑quality pulses. No defined taxonomic relationships based on echolocation pulses were identified. The variation in pulse shape was explained by the variables peak frequency and bandwidth, according to the PCA analysis. Cluster analysis formed four acoustic groups with no clear relationship to taxonomic, evolutionary, or ecological traits. Feeding acoustic libraries such as "Mashu Peru" will be crucial to more accurately describe the echolocation pulses of each species, better understand bioacoustic plasticity, and its sensitivity to methodological, environmental, and geographic factors. This study establishes a precedent for future research while contributing to bat conservation strategies.